2017
DOI: 10.1590/1981-22562017020.170083
|View full text |Cite
|
Sign up to set email alerts
|

Coping strategies used by the elderly regarding aging and death: an integrative review

Abstract: Objective: to identify and synthesize studies that approach the coping strategies used by the elderly to deal with aging and death. Method: an integrative review was performed in seven databases with the following descriptors: psychological adaptation, the elderly, death and aging. Results: 73 articles were identified. After applying the inclusion and exclusion criteria, six articles that identified multiple losses experienced by the elderly and included coping strategies were selected and analyzed. The main l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
20
2
9

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 12 publications
4
20
2
9
Order By: Relevance
“…These feelings may be unfavorable to maintaining the mental health of the elderly. In this sense, despite susceptible conditions related to working capacity of the elderly, systematic review performed in one study did not corroborate the findings of this research, as it indicates that work, even though associated with body damage and difficulty in performing functions, it acts as an important protective factor against depression, disability and frailty, maintaining well-being, good cognitive level and independence in daily activities (26)(27) .…”
Section: Discussioncontrasting
confidence: 63%
See 1 more Smart Citation
“…These feelings may be unfavorable to maintaining the mental health of the elderly. In this sense, despite susceptible conditions related to working capacity of the elderly, systematic review performed in one study did not corroborate the findings of this research, as it indicates that work, even though associated with body damage and difficulty in performing functions, it acts as an important protective factor against depression, disability and frailty, maintaining well-being, good cognitive level and independence in daily activities (26)(27) .…”
Section: Discussioncontrasting
confidence: 63%
“…Although depression is among the diseases that most affect the mental health of the elderly, the results of the present study showed that the higher the total score of depressive symptoms, the lower the total MMSE score, thus the greater the cognitive deficit. Although depression is a disabling mental disorder responsible for the loss of autonomy, functionality and aggravation of other disorders, and directly affects the quality of life, it is still underdiagnosed because health professionals believe that their symptoms are typical of aging (27,35) .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, studies have reported that women experience more fear and anxiety ( 45 , 46 ); however, they are more resilient and deal well in difficult times ( 33 ). Besides this, some aging people are at lower risk of COVID-19 fear ( 32 , 34 ), which can be attributed to these adults' resilience and coping strategies ( 47 , 48 ). Furthermore, older adults' successful involvement in community and family-related activities, favorable physical and mental health would have contributed to their resilience resulting in less fear in the older population in comparison with the younger populations – which is suggested to focus on policy actions.…”
Section: Discussionmentioning
confidence: 99%
“…Sin embargo, esta búsqueda es tan intensa que a menudo terminan rindiendo toda resolución del problema al poder de lo divino, ya que están tan agotados debido al proceso de envejecimiento en sí y sus consecuencias. Por lo tanto, al evaluar el afrontamiento de R/E a través del afrontamiento de esta investigación, se notó que las personas mayores de 50 años presentaban una mayor posición negativa hacia Dios, transfiriendo toda la responsabilidad de curar la enfermedad, sin ningún esfuerzo (22,23) .…”
Section: Discussionunclassified